Characterisation of physicochemical parameters in waters serving as habitats for stoneworts (Charales) in anthropogenic reservoirs of the Dąbrowa Basin - Ratajczak, Ewelina (Acta Geographica Lodziensia, 2024)
Anthropogenic activity significantly transforms components of the natural environment. The area of the Dąbrowa Basin has been heavily altered by long-term industrial activities, primarily mining. As a result, numerous excavations and sinkholes have been created, many of which have been largely reclaimed as water bodies. Despite substantial anthropogenic pressure, such water bodies can serve as habitats for valuable fauna and flora species. The article presents the results of chemical analyses of waters in selected anthropogenic reservoirs within the Dąbrowa Basin and assesses whether stonewort communities (Charales) still occur in these areas. The conducted research shows a high ability of stonewort to adapt to the changing parameters of reservoir waters.